Preparation method and application of series of zirconium-based MOFs and electrochromic film thereof
By using specific ligands and zirconium metal nodes in metal organic frame materials, combined with solvothermal method and post-synthetic modification technology, the problem of difficult electrochromic behavior regulation in the prior art is solved, and efficient and stable electrochromic performance and color regulation are achieved.
Patent Information
- Application Number
- CN202411633635.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art has problems such as difficulty, long cycles, high capital investment and low success rate in regulating electrochromic behavior.
Using zirconium metal as the node, 5',5"-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid) was used as the organic ligand, and metal organic frame material with a CSS topology and one-dimensional mesoporous channel was synthesized by solvothermal method, and post-synthetic modification was performed to install the linear dicarboxylic acid ligand TPDC-X.
It realizes simple, efficient and low-cost electrochromic behavior regulation. The material still maintains the original crystal phase after 10 electrochromic cycles, providing stable electrochromic performance and color regulation strategies.
Smart Images

Figure CN119613745A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochromic metal organic framework materials and film preparation. Specifically, it relates to a method based on 5', 5"-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid) (H 4 Synthesis and electrochromic applications of two mesoporous zirconium-based metal-organic framework materials and films with NDTB) as ligands. Background Art
[0002] Metal-organic frameworks (MOFs) are porous crystalline materials with an ordered and repetitive structure, consisting of metal ions / clusters and organic ligands connected by periodic connections. Their unique advantages enable MOFs to be used in many cutting-edge fields, such as gas adsorption / separation, smart sensors, energy catalysis, and biomedicine. Among them, stimuli-responsive MOFs can change their physicochemical properties in response to external stimuli (including temperature, force, light, and electricity), and are ideal candidates for designing smart functional materials. In particular, electrochromic MOFs undergo stable and reversible color changes when stimulated by an applied electric field, which is used in anti-glare rearview mirrors, smart windows, optical displays, and other rich applications. MOFs are undoubtedly recognized as one of the hot spots in the study of electrochromic materials. Due to its highly ordered porous structure, the entire framework of the electrochromic MOF can be in direct contact with the electrolyte. At the same time, the diffusion of ions in the electrolyte and the transfer of electrons in the process can be greatly improved, thereby promoting effective electrochromic conversion. Furthermore, the outstanding tunability and designability of MOF structures allow for a variety of electrochromic behaviors, and various redox units have been used to construct electrochromic MOFs. The team firstly passed Zn 2+ Electrochromic MOF films were prepared by the solvothermal reaction of ions with ligands containing naphthalene diimide (NDI). By grafting different functional groups on the ligands, they were able to further tune the color changes of these MOFs. et al. constructed two mesoporous electrochromic MOF-74-like MOFs films inserted with naphthalene dicarboxylic acid imide, showing rapid and reversible color transitions. In addition, the design of mesoporous MOFs facilitates the separation and embedding of ions in the electrolyte, promoting efficient electron transfer during the electrochromic process. Wang et al. developed MOF-74-type materials, introduced perylene tetracarboxylic dianhydride (PDI) units, and achieved ideal electrochromic properties with excellent electrochemical stability. In addition to NDI- and PDI-based ligands, Farha and Hupp et al. introduced pyrene-containing linkers for the construction of NU-901 electrochromic films. Similarly, ligands featuring viologen, triphenylamine or triphenylamine have also been used to design MOF films with different electrochromic properties. However, current methods for modifying the electrochromic properties of MOFs can only be achieved through de novo synthesis, resulting in time-consuming design cycles, high capital investment, and low success rates. Therefore, there is an urgent need to develop simple, fast, and effective methods to tune the electrochromic properties of specific MOFs. Summary of the invention
[0003] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing strategies for controlling electrochromic behavior, such as difficulty and long cycle, high capital investment and low success rate, and to provide a simple, efficient and low-cost electrochromic behavior control strategy;
[0004] The second object of the present invention is to provide a method for synthesizing the above-mentioned metal organic framework material and thin film;
[0005] The third object of the present invention is to provide the application of the above metal organic framework material in electrochromism;
[0006] The present invention uses zirconium metal as a node and uses 5',5"-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid) (H 4 A metal organic framework material with a csq topological structure and one-dimensional mesoporous channels was synthesized by solvothermal method using NDTB as an organic ligand and N,N-dimethylformamide as solvent. In addition, the above material was post-synthesized to synthesize another metal organic framework material containing different redox centers.
[0007] Based on the above purpose, the technical solution adopted by the present invention is:
[0008] Two mesoporous zirconium-based metal organic framework materials, characterized in that the metal is Zr, 5',5"-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid), referred to as H 4 NDTB, as a ligand, all the carboxylic acid groups in the ligand participate in the coordination and coordinate with zirconium metal to form a metal-organic framework material. The framework structure is a three-dimensional network structure containing one-dimensional mesoporous channels.
[0009] The two mesoporous zirconium-based metal organic framework materials have hexagonal lattice characteristics, and the space group is P 6 / mmm; the unit cell parameters of the materials are a=b=40.285, c=23.6990, α=β=90°, γ=120°, and a=b=40.54, c=23.45, α=β=90°, γ=120°, respectively. The pore types of the two materials are triangular micropores of 1.2nm and one-dimensional hexagonal mesopores of 2.7nm.
[0010] The synthesis method of the two mesoporous zirconium-based metal organic framework materials and thin films thereof is characterized by comprising the following steps:
[0011] (1) Preparation of 2,6-dibromo-4-nitrophenol:
[0012] Dissolve 4-nitrophenol, 4-methylbenzenesulfonic acid, potassium bromide and NBS in water, stir the mixture at 40°C for 2 hours, cool the reaction to room temperature, filter to obtain a solid, wash with an aqueous sodium metabisulfite solution, and dry to obtain the product;
[0013] (2) Preparation of 1,3-dibromo-2-methoxy-5-nitrobenzene:
[0014] The compound 2,6-dibromo-4-nitrophenol, methyl iodide and K 2 CO 3 The reaction mixture was heated to reflux for 18 h, then cooled to room temperature, the acetonitrile was removed using a rotary evaporator, the resulting mixture was poured into water and extracted with dichloromethane, and the combined organic layers were heated over anhydrous MgSO before the solvent was removed again using a rotary evaporator. 4 After drying on 400 μl and purification by column chromatography on silica gel using hexane as eluent and evaporation of the fractions containing the product, a white powdery compound was obtained as the product;
[0015] (3) Preparation of 3,5-dibromo-4-methoxyaniline:
[0016] Iron and NH 4Cl was added to a 100 ml round bottom flask, followed by H 2 O, the mixture was stirred and refluxed in an oil bath at 100°C for 30 minutes, and then 1,3-dibromo-2-methoxy-5-nitrobenzene was added. After the reaction was completed, the reaction mixture was diluted with dichloromethane, and then washed with water, dried over anhydrous sodium sulfate and filtered, and the solvent was evaporated under vacuum to obtain a yellow solid as 3,5-dibromo-4-methoxyaniline;
[0017] (4) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester:
[0018] 3,5-dibromo-4-methoxyaniline, (4-(ethoxycarbonyl)phenyl)boronic acid, K 2 CO 3 and tetrakis(triphenylphosphine)palladium were added to a 500 mL Schlenk flask equipped with a stirring bar, 1,4-dioxane was transferred into the system, and the reaction mixture was heated under N 2 The reaction mixture was heated to 85 °C under a 4% CO atmosphere for 72 h. After the reaction mixture was cooled to room temperature, the organic solvent was removed using a rotary evaporator. The resulting mixture was poured into water and extracted with dichloromethane. The combined organic layers were washed with anhydrous MgSO 4 After drying, the solvent was removed again using a rotary evaporator, and after purification by column chromatography on silica gel using ethyl acetate / hexane in a ratio of 1:4=v / v as eluent and evaporating the product-containing fractions, 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester was obtained as a pale yellow solid;
[0019] (5) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid:
[0020] Dissolve 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester in tetrahydrofuran, add an aqueous NaOH solution thereto, stir the mixture under reflux for 10 hours, then remove the organic solvent using a rotary evaporator, acidify the aqueous phase to pH=2 using an aqueous HCl solution, collect the resulting precipitate by filtration, wash with water, and dry under vacuum to obtain 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid;
[0021] (6) 5',5'-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid)(H4 Preparation of NDTB:
[0022] 5'-Amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid and 1,4,5,8-naphthalenetetracarboxylic anhydride were added to a 250 mL Schlenk flask equipped with a stirring bar, degassed N,N-dimethylformamide (DMF) was transferred into the system, and the reaction mixture was stirred at N 2 The mixture was heated to 160°C under an atmosphere for 12 hours. After the reaction mixture was cooled to room temperature, hydrochloric acid was added to the product for acidification, and then poured into water. The product was collected by filtration, washed with water, ethanol and acetone, and dried under vacuum to obtain a light yellow solid as the ligand H 4 NDTB;
[0023] (7) Preparation of linear dicarboxylic acid TPDC-X:
[0024] Step 1:
[0025] p-Bromobenzene / 1,4-dibromo-2,3,5,6-tetramethylbenzene / 9,10-dibromoanthracene / 4,7-dibromobenzo[c][1,2,5]thiadiazole / 2,5-dibromopyridine / 1,4-dibromo-2,5-dimethoxybenzene, (4-(ethoxycarbonyl)phenyl)boric acid / (4-(ethoxycarbonyl)-3,5-difluorophenyl)boric acid, cesium carbonate and tetrakis(triphenylphosphine)palladium were added into a 500 mL Schlenk flask equipped with a stirring magnetic bar. Degassed 1,4-dioxane was transferred into the system and the reaction mixture was stirred under N 2 The reaction mixture was heated to 85 °C for 72 h under a 2% CO atmosphere. After the reaction mixture was cooled to room temperature, the organic solvent was removed using a rotary evaporator. The resulting mixture was poured into water and extracted with dichloromethane. The combined organic layers were washed with anhydrous MgSO 4 After drying, the solvent was removed again using a rotary evaporator, using ethyl acetate / hexane in a ratio of 1:4 = v / v as the eluent, and after purification by column chromatography on silica gel and evaporation of the product-containing fractions, the compound 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4' -triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl) dibenzoate / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl) dibenzoate / 4,4'-(pyridine-2,5-diyl) dibenzoate / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester;
[0026] Step 2:
[0027] The compounds 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl)dibenzoate / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoate / 4,4'-(pyridine-2,5-diyl)dibenzoate / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester are dissolved in tetrahydrofuran, and an aqueous sodium hydroxide solution is added thereto. The mixture was stirred under reflux for 10 hours, and then the organic solvent was removed using a rotary evaporator, the aqueous phase was acidified to pH = 2 using aqueous hydrochloric acid, and the resulting precipitate was collected by filtration, washed with water, and dried under vacuum to obtain 3,3", 5,5"-tetrafluoro-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid / 2', 3', 5', 6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid / 4,4'-(anthracene-9 ,10-diyl)dibenzoic acid / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoic acid / 4,4'-(pyridine-2,5-diyl)dibenzoic acid / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid, the above ligand is named TPDC-X, X represents different substituents modified on TPDC, including but not limited to 4Me, 4F, TDA, AN, Py or 2OMe;
[0028] (8) Synthesis of NKM-908: Ligand H 4 NDTB, zirconium metal salt and benzoic acid are dissolved in an organic solvent, fully mixed, and then subjected to a solvothermal reaction at 80-150°C. After the reaction, the temperature is cooled to room temperature to obtain light yellow powder crystals, which are then washed and dried to obtain a metal organic framework material;
[0029] (9) Synthesis of NKM-908-TPDC-X: Dissolve the linear dicarboxylic acid ligand TPDC-X in an organic solvent, where X represents different substituents modified on the side chain of the linear dicarboxylic acid ligand. Then, add NKM-908 into the organic solvent, react at 80-150°C, wash and dry to obtain a metal organic framework material.
[0030] (10) Synthesis of NKM-908 thin film: Ligand H 4 NDTB, zirconium metal salt and benzoic acid are dissolved in an organic solvent, ultrasonically mixed, inserted into an ITO conductive glass sheet, and subjected to a solvothermal reaction at 80-150°C. After the reaction is completed, the temperature is lowered to room temperature to obtain a metal organic framework film on the ITO.
[0031] (11) Synthesis of NKM-908-TPDC-X film: The linear dicarboxylic acid ligand TPDC-X was dissolved in an organic solvent, and then the NKM-908 film was placed therein. After the reaction at 80-150°C, the film was washed and dried to obtain a metal organic framework film.
[0032] The organic solvent is N, N-dimethylformamide or N, N-dimethylacetamide; the zirconium metal salt is selected from zirconium oxychloride octahydrate or anhydrous zirconium chloride.
[0033] Ligand H 4 The molar ratio of NDTB to the zirconium metal salt is 1:5-30.
[0034] When synthesizing zirconium-based metal organic framework materials, the ratio of zirconium chloride to organic solvent and benzoic acid is 20 mg: 1-4 ml: 300-800 mg, preferably 20 mg: 3 ml: 500 mg;
[0035] When synthesizing the zirconium-based metal organic framework film, the usage ratio of zirconium oxychloride octahydrate to the organic solvent and benzoic acid is 90 mg: 5-15 ml: 800-1600 mg, preferably 90 mg: 10 ml: 1000 mg.
[0036] The temperature of the solvent thermal reaction for synthesizing the two mesoporous zirconium-based metal organic framework powder materials is 100-130°C, and the time is 1 to 4 days; the temperature of the solvent thermal reaction for synthesizing the film is 80-130°C, and the time is 30 minutes to 3 days.
[0037] The synthesis method of the two mesoporous zirconium-based metal organic framework materials and thin films thereof is characterized in that:
[0038] Ligand H 4 The usage ratio of NDTB to the organic solvent is 90 mg:5-15 ml, preferably 80 mg:10 ml.
[0039] The present invention further protects the application of the two mesoporous zirconium-based metal organic framework materials in electrochromism.
[0040] The beneficial effects of the present invention are:
[0041] (1) The ligand designed in the present invention has both redox activity and a saturated uncoordinated open window. The metal organic framework material formed by the self-assembly of the designed ligand and zirconium metal has a suitable pore size, which greatly facilitates the release and insertion of electrolyte cations during the electrochromic process. In addition, the presence of the saturated uncoordinated open window makes post-synthetic modification possible, and the linear dicarboxylic acid ligand TPDC-X is installed into the original MOF, which changes the electrochromic color change, thereby providing a simple and efficient electrochromic color regulation strategy.
[0042] (2) One of the zirconium-based metal-organic framework materials designed in the present invention has a CSQ topological structure, which makes the material have good stability. After 10 electrochromic cycles, it can still maintain the original crystal phase, which provides a reliable guarantee for the commercialization process of this type of material in the electrochromic process.
[0043] This material largely meets the current problem of difficult, time-consuming and labor-intensive color control in the design of electrochromic MOF materials, and both zirconium-based metal organic framework materials have shown great potential for stable electrochromic cycles. This invention provides new ideas for the design of subsequent metal organic framework materials and greatly promotes the practical application of metal organic framework materials in the field of electrochromism. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagram of the synthesis of the organic ligand used in the material in Example 1.
[0045] Figure 2 Schematic diagram of the synthesis of the TPDC-X organic ligand used in the present invention.
[0046] Figure 3 The NKM-908 material is respectively along c( Figure 3 a) and a( Figure 3 b) Crystal structure diagram of the axis.
[0047] Figure 4 The NKM-908-TPDC-X materials are respectively along c( Figure 4 a) and a( Figure 4 b) Crystal structure diagram of the axis.
[0048] Figure 5 It is a topological structure diagram of the NKM-908 material.
[0049] Figure 6 It is a topological structure diagram of the NKM-908-TPDC-X material.
[0050] Figure 7 is the X-ray powder diffraction pattern (XRD) of the NKM-908 and NKM-908-TPDC-X materials.
[0051] Figure 8 is the X-ray powder diffraction pattern (XRD) of the NKM-908 and NKM-908-TPDC-X films.
[0052] Fig. 9 is the 77K nitrogen isothermal full adsorption curve of the NKM-908 and NKM-908-TPDC-X materials ( Figure 3 a) and pore size distribution
[0053] Fig.10 The pore size distribution diagram of the NKM-908 and NKM-908-TPDC-X materials is shown in Figure 2.
[0054] Fig.11 is the electrochromic performance diagram of the NKM-908 material, Fig.11 a is the cyclic voltammetry curve, Fig.11 b is the in-situ UV-visible spectrum. Fig.11 c is the color at a specific voltage when CV is scanned.
[0055] Fig.12 is the electrochromic performance diagram of the NKM-908-TPDC-X material, Fig.12 a is the cyclic voltammetry curve of NKM-908-TPDC-2OMe, Fig.12 b is the in-situ UV-visible spectrum of NKM-908-TPDC-2OMe. Fig.12 c is the color of NKM-908-TPDC-2OMe under CV scanning to a specific voltage; Fig.12 d is the cyclic voltammetry curve of NKM-908-TPDC-4F, Fig.12 e is the in-situ UV-visible spectrum of NKM-908-TPDC-4F, Fig.12 f is the color of NKM-908-TPDC-4F under CV scanning to a specific voltage; Fig.12 g is the cyclic voltammetry curve of NKM-908-TPDC-4Me, Fig.12 h is the in-situ UV-visible spectrum of NKM-908-TPDC-4Me, Fig.12 i is the color of NKM-908-TPDC-4Me when CV scans to a specific voltage.
[0056] Fig.13 is the electrochromic performance diagram of the NKM-908-TPDC-X material, Fig.13 a is the cyclic voltammetry curve of NKM-908-TPDC-TDA, Fig.13 b is the in-situ UV-visible spectrum of NKM-908-TPDC-TDA, Fig.13 c is the color of NKM-908-TPDC-TDA under CV scanning to a specific voltage; Fig.13 d is the cyclic voltammetry curve of NKM-908-TPDC-AN, Fig.13 e is the in-situ UV-visible spectrum of NKM-908-TPDC-AN, Fig.13 f is the color of NKM-908-TPDC-AN when CV scanned to a specific voltage; Fig.13 g is the cyclic voltammetry curve of NKM-908-TPDC-Py, Fig.13 h is the in-situ UV-visible spectrum of NKM-908-TPDC-Py, Fig.13 i is the color of NKM-908-TPDC-Py when CV scanned to a specific voltage.
[0057] Fig.14 It is a cycle stability test chart of the NKM-908 and NKM-908-TPDC-X materials. DETAILED DESCRIPTION
[0058] Embodiment 1:
[0059] (1) Preparation of 2,6-dibromo-4-nitrophenol:
[0060] 4-Nitrophenol (2.78 g, 20 mmol), 4-methylbenzenesulfonic acid (7.61 g, 44.2 mmol), potassium bromide (7.14 g, 60 mmol) and NBS (7.12 g, 40 mmol) were dissolved in 50 mL of water and the mixture was stirred at 40°C for 2 hours. The reaction was cooled to room temperature, filtered to obtain a solid, washed with sodium metabisulfite aqueous solution (3×100 mL), and dried to obtain the product (4.22 g, yield: 71%). 1 H NMR (400 MHz, DMSO-d 6 )δ8.38(s, 2H)ppm, 11.04(s, 1H).
[0061] (2) Preparation of 1,3-dibromo-2-methoxy-5-nitrobenzene:
[0062] Compound 2,6-dibromo-4-nitrophenol (5.94 g, 20 mmol), methyl iodide (3.8 mL, 60 mmol) and K 2 CO 3 (4.14 g, 30 mmol) was dissolved in 100 mL of acetonitrile. The reaction mixture was heated to reflux for 18 hours and then cooled to room temperature. The acetonitrile was removed using rotary evaporation, and the resulting mixture was poured into water and extracted with dichloromethane (3×100 mL). The combined organic layers were heated to 4% by volume and then concentrated to 1% by volume before the solvent was removed again using a rotary evaporator. 4 After purification by column chromatography on silica gel using hexane as eluent and evaporation of the product-containing fractions, the compound was obtained as a white powder as the product (4.31 g, yield: 70%). 1 H NMR (400 MHz, CDCl 3 )δ3.98(s, 3H), 8.42(s, 2H)ppm.
[0063] (3) Preparation of 3,5-dibromo-4-methoxyaniline:
[0064] Iron (5 g, 89.2 mmol) and NH 4 Cl (3.6 g, 66 mmol) was added to a 100 mL round-bottom flask, followed by 10 mL of H 2 O. The mixture was stirred and refluxed in an oil bath at 100 ° C for 30 minutes, and then 1,3-dibromo-2-methoxy-5-nitrobenzene (6.84 g, 22 mmol) was added. After the reaction was completed, the reaction mixture was diluted with 100 mL of dichloromethane, then washed with water (50 mL) in sequence, dried over anhydrous sodium sulfate and filtered, and the solvent was evaporated under vacuum. A yellow solid was obtained as 3,5-dibromo-4-methoxyaniline. (4.55 g, yield: 74%). 1 H NMR (400 MHz, CDCl 3 ): δ3.78 (s, 3H), 5.33 (s, 2H), 6.80 (s, 1H) ppm.
[0065] (4) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester:
[0066] 3,5-dibromo-4-methoxyaniline (4.2 g, 15 mmol), (4-(ethoxycarbonyl)phenyl)boronic acid (8.73 g, 45 mmol), K 2 CO 3 (8.28 g, 60 mmol) and tetrakis(triphenylphosphine)palladium (0.867 g, 0.75 mmol) were added to a 500 mL Schlenk flask equipped with a stirring bar. 200 mL of 1,4-dioxane was transferred to the system. The reaction mixture was heated under N 2 The reaction mixture was heated to 85°C under an atmosphere for 72 hours. After the reaction mixture was cooled to room temperature, the organic solvent was removed using a rotary evaporator, and the resulting mixture was poured into water and extracted with dichloromethane (3×50 mL). The combined organic layers were washed with anhydrous MgSO 4 After drying, the solvent was removed again using a rotary evaporator. After purification by column chromatography on silica gel using ethyl acetate / hexane (1:4=v / v) as eluent and evaporating the fraction containing the product, 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (4.27 g, yield: 68%) was obtained as a light yellow solid. 1 H NMR (400MHz, CDCl3): δ1.40 (t, 6H), 4.40 (q, 4H), 5.16 (s, 2H), 6.71 (s, 2H), 7.66 (d, 4H).
[0067] (5) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid:
[0068] 5'-amino-2'-methoxy-[1,1'-:3'-, 1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (0.58g, 1.4mmol) was dissolved in 20mL tetrahydrofuran, to which 30mL 10M NaOH aqueous solution was added. The mixture was stirred at reflux for 10 hours, and then the organic solvent was removed using a rotary evaporator. The aqueous phase was acidified to pH=2 using a 6M HCl aqueous solution. The resulting precipitate was collected by filtration, washed with water (200mL), and dried under vacuum to give 5'-amino-2'-methoxy-[1,1'-:3'-, 1'-triphenyl]-4,4'-dicarboxylic acid (0.457g, 90%). 1 H NMR (400MHz, CDCl3): δ2.95 (s, 3H), 5.17 (s, 2H), 6.63 (s, 2H), 7.67 (d, 4H), 7.99 (d, 4H), 12.91 (s, 2H) ppm.
[0069] (6) 5',5'-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid)(H 4 Preparation of NDTB:
[0070] 5'-Amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid (3.64 g, 10 mmol) and 1,4,5,8-naphthalene tetracarboxylic anhydride (1.34 g, 5.0 mmol) were added to a 250 mL Schlenk flask equipped with a stirring bar. 50 mL of degassed N,N-dimethylformamide (DMF) was transferred to the system. The reaction mixture was heated at N 2 The mixture was heated to 160°C under a nitrogen atmosphere for 12 hours. After the reaction mixture was cooled to room temperature, 5 mL of 1 mol / L hydrochloric acid was added to the product for acidification, and then the product was poured into 500 mL of water. The product was collected by filtration, washed with water, ethanol and acetone, and dried under vacuum to obtain a light yellow solid as the ligand H. 4 NDTB (3.95 g, yield = 82.3%). 1 H NMR (400MHz, DMSO-d6) δ3.19 (s, 6H), 7.64 (s, 4H), 7.75 (d, 8H), 8.05 (d), 8.68 (d, 8H), 13.02 (s, 4H) ppm. .
[0071] (7) Preparation of linear dicarboxylic acid TPDC-X:
[0072] Step 1:
[0073] p-Bromobenzene / 1,4-dibromo-2,3,5,6-tetramethylbenzene / 9,10-dibromoanthracene / 4,7-dibromobenzo[c][1,2,5]thiadiazole / 2,5-dibromopyridine / 1,4-dibromo-2,5-dimethoxybenzene (5 mmol), (4-(ethoxycarbonyl)phenyl)boric acid / (4-(ethoxycarbonyl)-3,5-difluorophenyl)boric acid (15 mmol), cesium carbonate (20 mmol) and tetrakis(triphenylphosphine)palladium (0.25 mmol) were added to a 500 mL Schlenk flask equipped with a stirring magnetic bar. 200 mL of degassed 1,4-dioxane was transferred to the system. The reaction mixture was heated under N 2 The reaction mixture was heated to 85°C for 72 hours under an atmosphere of 40 °C. After the reaction mixture was cooled to room temperature, the organic solvent was removed using a rotary evaporator, and the resulting mixture was poured into water and extracted with dichloromethane (3 × 50 mL). The combined organic layers were washed with anhydrous MgSO 4 Dry, then use a rotary evaporator to remove the solvent again. Use ethyl acetate / hexane (1:4=v / v) as eluent, after purification by column chromatography on silica gel and evaporation of the fraction containing the product, obtain compound 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl) dibenzoic acid diethyl ester / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl) dibenzoic acid diethyl ester / 4,4'-(pyridine-2,5-diyl) dibenzoic acid diethyl ester / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester.
[0074] 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (yield: 72%). 1 HNMR (400MHz, CDCl 3 ): δ7.93(s,4H),7.71(d,4H),4.34(q,4H),1.28(t,6H)ppm.
[0075] 2',3',5',6'-Tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (yield: 70%). 1 HNMR (400MHz, CDCl 3): δ1.30(t,6H),1.92(s,12H),4.36(q,4H),7.30(d,4H),8.16(d,4H)ppm.
[0076] Diethyl 4,4'-(Anthracene-9,10-diyl)dibenzoate (yield: 64%). 1 H NMR (400 MHz, CDCl 3 ): δ1.50(t,6H),4.51(q,4H),7.39(d,4H),7.61(d,4H),7.64(d,4H),8.32(d,4H)ppm.
[0077] Diethyl 4,4'-(Benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoate (yield: 66%). 1 H NMR (400 MHz, CDCl 3 ): δ1.46(t,6H),4.45(q,4H),7.89(d,2H),8.10(d,4H),8.24(d,4H)ppm.
[0078] Diethyl 4,4'-(pyridine-2,5-diyl)dibenzoate (yield: 64%). 1 H NMR (400 MHz, CDCl 3 ): δ1.36(t,6H),4.36(q,4H),7.66(d,2H),7.83(d,1H),7.95(d,1H),8.05(d,2H),8.10(d,2H),8.12(d,2H),8.92(s,1H)ppm.
[0079] 2',5'-Dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (yield: 67%). 1 H NMR (400 MHz, CDCl 3 ): δ1.44(t,6H),3.83(s,6H),4.44(q,4H),7.02(s,2H),7.69(d,4H),8.13(d,4H)ppm.
[0080] Step 2:
[0081] Compound 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl) dibenzoic acid diethyl ester / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl) dibenzoic acid diethyl ester / 4,4'-(pyridine-2,5-diyl) dibenzoic acid diethyl ester / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester (1.4 mmol) was dissolved in 20 mL of tetrahydrofuran, and 30 mL of 10M sodium hydroxide aqueous solution was added thereto. The mixture was stirred under reflux for 10 hours, and then the organic solvent was removed using a rotary evaporator. The aqueous phase was acidified to pH = 2 using aqueous hydrochloric acid. The resulting precipitate was collected by filtration, washed with water (200 mL), and dried under vacuum to give 3,3", 5,5"-tetrafluoro-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid / 2', 3', 5', 6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid / 4,4'-(anthracene-9,10-diyl)dibenzoic acid / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoic acid / 4,4'-(pyridine-2,5-diyl)dibenzoic acid / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid. The above ligands are named TPDC-X, where X represents different substituents modified on TPDC, such as 4Me, 4F, TDA, AN, Py and 2OMe.
[0082] 3,3",5,5"-tetrafluoro-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid (yield: 91%). 1 H NMR (400 MHz, DMSO-d 6 ): δ13.93(s,2H),7.96(s,4H),7.68(d,4H)ppm.
[0083] 2',3',5',6'-Tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid (yield: 93%). 1 HNMR (400 MHz, DMSO-d 6 ): δ1.83(s,12H),7.26(d,4H),8.02(d,4H),13.01(s,2H)ppm.
[0084] 4,4'-(Anthracene-9,10-diyl)dibenzoic acid (yield: 93%). 1 HNMR (400 MHz, DMSO-d 6): δ7.48(d,4H),7.55(d,4H),7.63(d,4H),8.22(d,4H),13.14(s,2H)ppm.
[0085] 4,4'-(Benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoic acid (yield: 94%). 1 H NMR (400 MHz, DMSO-d 6 ): δ8.10(d,2H),8.15(d,4H),8.17(d,4H),13.04(s,2H)ppm.
[0086] 4,4'-(Pyridine-2,5-diyl)dibenzoic acid (yield: 94%). 1 HNMR (400 MHz, DMSO-d 6 ): δ7.98(d,1H),8.04(d,2H),8.09(d,3H),8.22(d,2H),8.31(d,2H),9.12(s,1H),13.02(s,2H)ppm.
[0087] 2',5'-Dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid (yield: 90%). 1 H NMR (400 MHz, DMSO-d 6 ): δ3.80(s,6H),7.13(s,2H),7.73(d,4H),8.02(d,4H),12.95(s,2H)ppm.
[0088] The above steps also refer to the attached Figure 1 and Figure 2 .
[0089] (8) Synthesis of NKM-908: Ligand H 4 NDTB (10 mg), zirconium chloride (20 mg) and benzoic acid (500 mg) were dissolved in 3 mL DMF and mixed thoroughly, and then subjected to solvent thermal reaction at 120 °C for 3 days. After the reaction, the temperature was cooled to room temperature to obtain light yellow powder crystals, which were washed and dried to obtain the metal organic framework material NKM-908.
[0090] (9) Synthesis of NKM-908-TPDC-X: 30 mg of linear dicarboxylic acid ligand TPDC-X (X represents different substituents modified on the side chain of the linear dicarboxylic acid ligand) was dissolved in DMF, and then 30 mg of NKM-908 was added thereto. The mixture was reacted at 100 °C for 1 day, and then washed and dried to obtain the metal organic framework material NKM-908-TPDC-X.
[0091] (10) Synthesis of NKM-908 film: 90 mg ligand H 4 NDTB, 90 mg zirconium oxychloride octahydrate and 1000 mg benzoic acid were dissolved in 10 mL DMF, ultrasonically mixed, inserted into an ITO conductive glass sheet, and subjected to solvothermal reaction at 120 °C for 3 days. After the reaction, the temperature was cooled to room temperature to obtain a NKM-908 metal organic framework film on ITO.
[0092] (11) Synthesis of NKM-908-TPDC-X film: 30 mg of linear dicarboxylic acid ligand TPDC-X was dissolved in an organic solvent, and then the NKM-908 film was placed therein. After reacting at 100 °C for 1 day, the film was washed and dried to obtain the NKM-908-TPDC-X metal organic framework film.
[0093] The present invention uses the following instruments or methods to characterize and test the performance of materials.
[0094] (1) Single crystal X-ray diffraction test was performed on NKM-908 material. Crystals were picked out from the mother liquor, transferred to oil, and mounted on a loop for single crystal X-ray diffraction test. Diffraction data were tested on a Rigaku XtalAB ProMM007DW diffractometer equipped at 100K. Data collection and reduction were performed using the CrystAlisPro program. The crystal structure of NKM-908 is shown in Figure 3 As shown (drawn using Dianond software).
[0095] (2) The NKM-908-TPDC-4F material was subjected to three-dimensional electron diffraction test. The electron diffraction data of the crystals of NKM-908-TPDC-4F were collected at room temperature using a Rigaku XtaLABSynergy ED, HyPix ED, and an electron source at 200keV diffractometer. The sample powder was dispersed in an ethanol solution and ultrasonically treated for 5 minutes, then dropped onto a copper grid, and 3D electron diffraction data were collected after the surface of the copper grid was completely dry. CrysAlisPro was used for data processing, ShelXT was used to solve all structures by the intrinsic phasing method, and ShelXL was used for refinement in the Olex2 graphical user interface. The crystal structure of NKM-908-TPDC-4F is shown in Figure 4 As shown (drawn using Dianond software).
[0096] (3) The topological structure of NKM-908 is calculated by ToposPro software. The topological structure of NKM-908 is as follows: Figure 5 As shown (drawn using Dianond software).
[0097] (4) The topological structure of NKM-908-TPDC-4F is calculated by ToposPro software. The topological structure of NKM-908-TPDC-4F is as follows: Figure 6 As shown (drawn using Dianond software).
[0098] (5) The powder X-ray diffraction (PXRD) patterns of the NKM-908 and NKM-908-TPDC-4F materials prepared by the present invention were collected on a Rigaku MiniFlex600 diffractometer equipped with a copper target. The powder X-ray diffraction patterns of the NKM-908 and NKM-908-TPDC-4F materials are shown in Figure 7 As shown (drawn using Origin software and simulated using Mercury software).
[0099] (6) The X-ray diffraction (PXRD) patterns of the NKM-908 and NKM-908-TPDC-4F material films prepared by the present invention were collected on a Rigaku MiniFlex600 diffractometer equipped with a copper target. Figure 8 As shown (drawn using Origin software and simulated using Mercury software).
[0100] (7) Micromeritics ASAP 2020 surface area and pore size analyzer was used to analyze N 2 Adsorption measurements. Low-pressure N adsorption of NKM-908 and NKM-908-TPDC-4F at 77 K was measured in a liquid nitrogen bath. 2 Adsorption isotherm. Test results are as follows Fig. 9 and Fig.10 As shown, the BET specific surface areas of NKM-908, NKM-908-TPDC-4Me, NKM-908-TPDC-2OMe, NKM-908-TPDC-AN, NKM-908-TPDC-TDA, NKM-908-TPDC-Py and NKM-908-TPDC-4F are 2924, 2196, 2291, 2125, 2569, 2566 and 2429 m 2 .g -1 The pore sizes are around 2.7nm and 1.2nm respectively, with triangular channels with a diameter of 1.2nm and hexagonal channels with a diameter of 2.7nm.
[0101] (8) The cyclic voltammetry curves of NKM-908 in the present invention were measured on a CHI760E, and all measurements were performed using a standard three-electrode system. All measurements were performed in an electrolyte solution of 0.1 M [( n Bu) 4N]PF 6 / DMF. The working electrode was NKM-908 thin film ITO electrode, the reference electrode was Ag / AgCl, and the platinum mesh electrode was used as the counter electrode. In-situ UV-visible spectroscopy test: A 10 mm long quartz cuvette was used to test the UV-visible spectrum of the thin film electrode, a platinum wire was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 0.1 M [( n Bu) 4 N]PF 6 / DMF is the electrolyte. The color change of the film during CV scanning was photographed using an iPhone 13.
[0102] Fig.11 a shows that the NKM-908 film has two different pairs of redox peaks, near -0.51V / -0.43V and -0.9V / -0.73V, respectively. Fig.11 c It can be observed that the almost colorless NKM-908 film shows two reversible color changes (light yellow and green) under the potential change during the CV scan. Fig.11 b is the in-situ UV-visible absorption spectrum to monitor the real-time changes of NKM-908 film. In the absence of an external electric field, the characteristic π-π* absorption bands of the NDI group at 364nm and 382nm were observed in the UV-vis spectrum of the NKM-908 film. During the application of the potential to -0.6V, these two peaks gradually decreased, while new absorption peaks appeared and enhanced at 475nm, 606nm, 706nm and 786nm, which correspond to the NDI ·- The formation of species corresponds to the first color of light yellow. When the potential is continuously applied to -1.4 V, NDI ·- Species continue to be reduced to NDI 2- When the potential rises to -1.4 V, the absorption peak at 475 nm decreases, while new absorption peaks appear at 398 nm, 422 nm, 575 nm and 625 nm, which increase as the potential rises to -1.4 V. Corresponding to the second color green.
[0103] (9) The cyclic voltammetry curves of NKM-908-TPDC-X in the present invention were measured on CHI760E, and all measurements were performed using a standard three-electrode system. All measurements were performed in an electrolyte solution of 0.1 M [( n Bu) 4 N]PF 6 / DMF. The working electrode was NKM-908-TPDC-X thin film ITO electrode, the reference electrode was Ag / AgCl, and the platinum mesh electrode was used as the counter electrode. In-situ UV-visible spectroscopy test: A 10 mm long quartz cuvette was used to test the UV-visible spectrum of the thin film electrode, a platinum wire was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 0.1 M [( n Bu) 4 N]PF 6 / DMF is the electrolyte. The color change of the film during CV scanning was photographed using an iPhone 13.
[0104] First, three non-redox linear dicarboxylic acid ligands, TPDC-2OMe, TPDC-4Me, and TPDC-4F, were successfully installed into NKM-908 films for study. The CV curves of NKM-908-TPDC-2OMe, NKM-908-TPDC-4Me, and NKM-908-TPDC-4F films showed no difference from those of NKM-908 ( Fig.12 a, d, g, the inset is the installed TPDC-X ligand), and two groups of redox peaks were detected at -0.51V / 0.43V and -0.9V / 0.73V, respectively. At the same time, their colors changed from light yellow to dark yellow and then to green ( Fig.12 c, f, i). However, in all the processes of the electrochromic process, the color of the film after the linker was installed was darker than that of NKM-908. In situ UV-visible spectroscopy revealed that the electrochromic groups NDI, NDI ·- and NDI 2- The characteristic absorption peak ( Fig.12 b, e, h).
[0105] The present invention further designs to install three TPDC ligands (TPDC-TDA, TPDC-AN and TPDC-Py) with redox activity in situ into the NKM-908 film. Different from the CV curve of the NKM-908 film, the NKM-908-TPDC-TDA film exhibits two groups of redox peaks with different peak positions, which are located at -0.9V / -0.73V and -1.42V / -1.3V ( Fig.13 a, the inset shows the installed TPDC-TDA ligand). The former group of peaks corresponds to the oxidation and reduction process of the NDI unit, while the latter group of peaks corresponds to the oxidation and redox process of the TDA component. During the CV process, the NKM-908-TPDC-TDA film exhibited a reversible color transition from light yellow to dark yellow, then to purple, and finally to green ( Fig.13 c), UV-visible spectra monitored simultaneously such as Fig.13As shown in Figure b, when the potential is applied from 0V to -1.1V, a gradual increase in the absorption band at 384nm can be observed. This observation is consistent with the characteristic π-π* absorption band of the NDI group, which corresponds to a gradual color change from light yellow to dark yellow. Interestingly, when the potential increases from -1.6V to -2V, a new absorption peak with a wavelength of 520nm appears at -1.6V and gradually weakens with the increase in potential. This new peak belongs to the purple state during the color change process, which is attributed to the single-electron reduction process of the TDA part. When the potential is further applied from -2V to -2.3V, the absorption peak at 520nm gradually weakens and disappears. At the same time, new absorption peaks are generated at 398nm, 422nm, 575nm and 625nm, which are attributed to NDI 2- , so the film turns green.
[0106] Two groups of redox peaks at -0.91 V / -0.77 V and -1.80 V / -1.97 V can be clearly observed in the CV curve of NKM-908-TPDC-AN film, which correspond to the redox of NDI and the redox of anthracene, respectively. Fig.13 d). During the CV scan, the color of the film changes from almost colorless to blue and then to light green ( Fig.13 f). In situ UV-Vis absorption spectroscopy to explore the color changes during electrochromic processes ( Fig.13 e). Without applying an electric potential, absorption peaks were detected at 356nm, 374nm, and 395nm, which are due to the characteristic absorption peaks of anthracene in TPDC-AN and the characteristic π-π* absorption band of NDI. As the potential increased to -1.1V, the absorption of the above three positions gradually increased, which was attributed to the characteristic absorption peaks when anthracene underwent redox reaction. When the potential was further changed to -2.2V, the film turned light green, and new absorption peaks appeared at 625nm, 575nm, and 422nm, indicating that NDI 2- formation.
[0107] Installing the TPDC Py linker also achieved electrochromic color tuning. Fig.13 g shows the CV curve of NKM-908-TPDC-Py film, and two groups of redox peaks (-0.9V / -0.73V and -2.16V / -2.04V) are clearly observed. The former group of peaks corresponds to the redox peaks of NDI unit, and the latter group of peaks belongs to the redox peaks of TPDC Py. At the same time, during the CV scan, the color of the film changes from almost colorless to dark yellow and then to dark pink at 0V, -1.1V and -2.2V ( Fig.13 i). Fig.13h is the in-situ UV-visible absorption spectrum of the tested NKM-908-TPDC-Py film. No absorption peak was detected for the NKM-908-TPDC-Py film at 0V. As the potential gradually increased to -1.1V, new absorption peaks appeared at 355nm and 378nm, and the intensity gradually increased along the process, which corresponds to the deep yellow state in electrochromism. During the following potential change from -1.1V to -2.2V, new absorption peaks were generated at 448nm, 488nm and 810nm, which correspond to the deep pink state in electrochromism.
[0108] (10) The cyclic stability curves of NKM-908 and NKM-908-TPDC-X in the present invention were tested on CHI760E and KU-T1810 of Kenfan Electronic Technology. All measurements were performed using a standard three-electrode system. A 10 mm long quartz cuvette was used as the container, the film was directly used as the working electrode, the platinum wire was used as the counter electrode, the Ag / AgCl was used as the reference electrode, and the 0.1 M [( n Bu) 4 N]PF 6 / DMF is the electrolyte.
[0109] The cycling stability of NKM-908, NKM-908-TPDC-2OMe, NKM-908-TPDC-4F and NKM-908-TPDC-4Me was measured by alternating cycling at 0 V and −1.4 V. The cycling stability of NKM-908-TPDC-TDA, NKM-908-TPDC-AN and NKM-908-TPDC-Py, Fig.14 It showed that no obvious attenuation was observed for NKM-908 and NKM-908-TPDC-X after 10 cycles.
[0110] It should be further explained that the above implementation modes are only used for understanding the technical solutions of the present invention, and are not used to limit the protection scope of the present invention. Any obvious adjustments and modifications made to the technical concepts of the present invention should also fall within the protection scope of the present invention.
Claims
1. Two mesoporous zirconium-based metal organic framework materials, characterized in that: The metal is Zr, and 5',5"-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid) (H4NDTB) is used as a ligand. All carboxylic acid groups in the ligand participate in the coordination and coordinate with zirconium to form a metal organic framework material. The framework structure is a three-dimensional network structure containing one-dimensional mesoporous channels.
2. The mesoporous zirconium-based metal organic framework material according to claim 1, characterized in that: The two mesoporous zirconium-based metal-organic framework materials have the lattice characteristics of the hexagonal crystal system, and the space group is P6 / mmm; the unit cell parameters of the materials are a=b=40.285, c=23.6990, α=β=90°, γ=120°, and a=b=40.54, c=23.45, α=β=90°, γ=120° respectively; the pore types of the two materials are 1.2nm triangular micropores and 2.7nm one-dimensional hexagonal mesopores.
3. The method for preparing two mesoporous zirconium-based metal organic framework material films according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of 2,6-dibromo-4-nitrophenol: Dissolve 4-nitrophenol, 4-methylbenzenesulfonic acid, potassium bromide and NBS in water, stir the mixture at 40°C for 2 hours, cool the reaction to room temperature, filter to obtain a solid, wash with an aqueous sodium metabisulfite solution, and dry to obtain the product; (2) Preparation of 1,3-dibromo-2-methoxy-5-nitrobenzene: The compound 2,6-dibromo-4-nitrophenol, methyl iodide and K2CO3 were dissolved in acetonitrile, the reaction mixture was heated to reflux for 18 hours, then cooled to room temperature, the acetonitrile was removed using rotary evaporation, the resulting mixture was poured into water and extracted with dichloromethane, the combined organic layers were dried over anhydrous MgSO4 before the solvent was removed again using a rotary evaporator, and purified by silica gel column chromatography using hexane as the eluent to obtain a white powdery product; (3) Preparation of 3,5-dibromo-4-methoxyaniline: Iron and NH4Cl were added to a 100 ml round bottom flask, followed by H2O, and the mixture was stirred and refluxed in an oil bath at 100°C for 30 minutes, followed by the addition of 1,3-dibromo-2-methoxy-5-nitrobenzene. After the reaction was complete, the reaction mixture was diluted with dichloromethane, then washed with water, dried over anhydrous sodium sulfate and filtered, and the solvent was removed by rotary evaporation to obtain a yellow solid as 3,5-dibromo-4-methoxyaniline; (4) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester: 3,5-dibromo-4-methoxyaniline, (4-(ethoxycarbonyl)phenyl)boric acid, K2CO3 and tetrakis(triphenylphosphine)palladium were added to a 500 mL Schlenk flask equipped with a stirring bar, 1,4-dioxane was transferred into the system, the reaction mixture was heated to 85°C under N2 atmosphere for reaction for 72 hours, the reaction mixture was cooled to room temperature, the organic solvent was removed by a rotary evaporator, the resulting mixture was poured into water and extracted with dichloromethane, the combined organic layer was dried over anhydrous MgSO4, and then the solvent was removed again by a rotary evaporator, and the mixture was purified by silica gel column chromatography using ethyl acetate / hexane with a volume ratio of 1:4 as an eluent to obtain 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester as a light yellow solid; (5) Preparation of 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid: Dissolve 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid diethyl ester in tetrahydrofuran, add an aqueous NaOH solution thereto, stir the mixture under reflux for 10 hours, then remove the organic solvent using a rotary evaporator, acidify the aqueous phase to pH=2 using an aqueous HCl solution, collect the resulting precipitate by filtration, wash with water, and dry under vacuum to obtain 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid; (6) Preparation of 5',5'-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(2'-methoxy-[1,1'-:3',1'-triphenyl]-4,4'-dicarboxylic acid) (H4NDTB): 5'-amino-2'-methoxy-[1,1'-:3'-,1'-triphenyl]-4,4'-dicarboxylic acid and 1,4,5,8-naphthalenetetracarboxylic anhydride were added to a 250 mL Schlenk flask equipped with a stirring bar, degassed N,N-dimethylformamide was transferred to the system, the reaction mixture was heated to 160° C. under N2 atmosphere for 12 hours, the reaction mixture was cooled to room temperature, hydrochloric acid was added to the product for acidification, and then it was poured into water, the product was collected by filtration, washed with water, ethanol and acetone, and dried under vacuum to obtain a light yellow solid as the ligand H4NDTB; (7) Preparation of linear dicarboxylic acid TPDC-X: Step 1: Add p-bromobenzene / 1,4-dibromo-2,3,5,6-tetramethylbenzene / 9,10-dibromoanthracene / 4,7-dibromobenzo[c][1,2,5]thiadiazole / 2,5-dibromopyridine / 1,4-dibromo-2,5-dimethoxybenzene, (4-(ethoxycarbonyl)phenyl)boric acid / (4-(ethoxycarbonyl)-3,5-difluorophenyl)boric acid, cesium carbonate and tetrakis(triphenylphosphine)palladium to a 500 mL stirring tube equipped with a magnetic stirrer. The degassed 1,4-dioxane was transferred to the system in a Schlenk flask, and the reaction mixture was heated to 85°C for 72 hours under a N2 atmosphere. After the reaction mixture was cooled to room temperature, the organic solvent was removed by a rotary evaporator, and the resulting mixture was poured into water and extracted with dichloromethane. The combined organic layer was dried over anhydrous MgSO4, and then the solvent was removed again by a rotary evaporator. The compound 3,3',5,5'-tetrafluoro-[1, 1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl)dibenzoic acid diethyl ester / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoic acid diethyl ester / 4,4'-(pyridine-2,5-diyl)dibenzoic acid diethyl ester / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester; Step 2: Compound 3,3',5,5'-tetrafluoro-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 2',3',5',6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester / 4,4'-(anthracene-9,10-diyl)dibenzoate / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoate / 4,4'-(pyridine-2,5-diyl)dibenzoate / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid diethyl ester was dissolved in tetrahydrofuran, and sodium hydroxide aqueous solution was added thereto. The mixture was stirred under reflux for 10 hours, and then the organic solvent was removed by a rotary evaporator. The aqueous phase was acidified to pH=2 with hydrochloric acid aqueous solution, and the reaction mixture was stirred under reflux for 10 hours. The resulting precipitate is collected by filtration, washed with water, and dried under vacuum to obtain 3,3", 5,5"-tetrafluoro-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid / 2', 3', 5', 6'-tetramethyl-[1,1':4'-triphenyl]-4,4'-dicarboxylic acid / 4,4'-(anthracene-9,10-diyl)dibenzoic acid / 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)dibenzoic acid / 4,4'-(pyridine-2,5-diyl)dibenzoic acid / 2',5'-dimethoxy-[1,1'-:4'-triphenyl]-4,4'-dicarboxylic acid. The above ligand is named TPDC-X, where X represents different substituents modified on TPDC, including but not limited to 4Me, 4F, TDA, AN, Py or 2OMe; (8) NKM-908 Synthesis: The ligand H4NDTB, zirconium metal salt and benzoic acid are dissolved in an organic solvent, mixed thoroughly, and then subjected to a solvothermal reaction at 80-150°C. After the reaction, the temperature is cooled to room temperature to obtain light yellow powder crystals, which are then washed and dried to obtain a metal organic framework material; (9) Synthesis of NKM-908-TPDC-X: Dissolve the linear dicarboxylic acid ligand TPDC-X in an organic solvent, where X represents different substituents modified on the side chain of the linear dicarboxylic acid ligand. Then, add NKM-908 into the organic solvent, react at 80-150°C, wash and dry to obtain a metal organic framework material. (10) NKM-908 film synthesis: The ligand H4NDTB, zirconium metal salt and benzoic acid are dissolved in an organic solvent, ultrasonically mixed, inserted into an ITO conductive glass sheet, and subjected to a solvothermal reaction at 80-150° C. After the reaction is completed, the temperature is lowered to room temperature to obtain a metal organic framework film on the ITO. (11) Synthesis of NKM-908-TPDC-X film: The linear dicarboxylic acid ligand TPDC-X was dissolved in an organic solvent, and then the NKM-908 film was placed therein. After the reaction at 80-150°C, the film was washed and dried to obtain a metal organic framework film.
4. The method for preparing two mesoporous zirconium-based metal organic framework material films according to claim 3, characterized in that: The organic solvent is N, N-dimethylformamide or N, N-dimethylacetamide; the zirconium metal salt is selected from zirconium oxychloride octahydrate or anhydrous zirconium chloride.
5. The method for preparing two mesoporous zirconium-based metal organic framework material films according to claim 3, characterized in that: The molar ratio of the ligand H4NDTB to the zirconium metal salt is 1:5-30.
6. The method for preparing two mesoporous zirconium-based metal organic framework material films according to claim 3, characterized in that: When synthesizing zirconium-based metal organic framework materials, the ratio of zirconium metal salt to organic solvent and benzoic acid is 20 mg: 1-4 ml: 300-800 mg, preferably 20 mg: 3 ml: 500 mg; When preparing the zirconium-based metal organic framework film, the usage ratio of zirconium metal salt to organic solvent and benzoic acid is 90 mg: 5-15 ml: 800-1600 mg, preferably 90 mg: 10 ml: 1000 mg.
7. The method for synthesizing two mesoporous zirconium-based metal organic framework material films according to claim 3, characterized in that: The temperature of the solvent thermal reaction for synthesizing powder materials is 100-130° C., and the time is 1 to 4 days; the temperature of the solvent thermal reaction for synthesizing thin films is 80-130° C., and the time is 30 minutes to 3 days.
8. The method for synthesizing two mesoporous zirconium-based metal organic framework material films according to claim 3, characterized in that: The usage ratio of the ligand H4NDTB to the organic solvent is 90 mg:5-15 ml, preferably 80 mg:10 ml.
9. Use of the two mesoporous zirconium-based metal organic framework material films according to claim 1 or 2 in electrochromism.
Citation Information
Patent Citations
Methods for producing metal-organic framework materials containing metals of subgroup IV
CN101426797A
Metal-organic zirconium-based framework materials
CN101426798A
Electrochromic film material based on porphyrin MOF and preparation method thereof
CN115079480A
Two isomorphic pentacyleneoctacarboxylic acid hydrogen bond organic framework composite materials with white light emission and preparation and application of two isomorphic pentacyleneoctacarboxylic acid hydrogen bond organic framework composite materials
CN117986611A